Cognitive impairment negatively impacts allied health service uptake: Investigating the association between health and service use. (March 2021) - MacLeod, Catherine A.; Bu, Feifei; Rutherford, Alasdair C.; Phillips, Judith; Woods, Robert; ,
Abstract: There is widespread concern about the potential impact on health and social care services of the ageing population and long-term health conditions, such as dementia. To effectively plan services it is important to understand current need and use and identify gaps in provision. Using data from the Cognitive Function and Ageing Study Wales (CFAS Wales), we used logistic regression to model the relationship between health (self-rated health, cognitive impairment, and activities of daily living), and the use of health and care services. CFAS Wales is a longitudinal cohort study of people aged 65 years and over, in two areas in Wales, UK, over-sampling those aged 75 years and over. Participants (n = 3593) answered a wide range of health and lifestyle questions and completed a variety of cognitive and physical health assessments. Data from 3153 people from wave 1 and 1968 people from wave 2 were analysed. As anticipated we found poorer health, on some indicators, predicted greater service use, including social care, hospital, general practitioner, and nursing services. However, cognitive impairment did not predict greater service use, except for social care. Controlling for age, sex, socio-economic status, social connection indices and area environment, conversely we found lower reported uptake of allied health services by people with cognitive impairment. Further analysis showed that people with a cognitive impairment were less likely to report having a sight-check or seeing a dentist in the previous year, a finding replicated in wave 2. These differences were not explained by transportation issues. In contrast, we did not find a significant difference in reported uptake of hearing checks or physiotherapist use, with mixed evidence of differences in chiropodist visits. Not accessing these preventative services may not only exacerbate existing conditions but have further downstream negative consequences for health and well-being in people who are cognitively impaired. Highlights: Medical and social care service use typically increased as health decreased. Allied health services uptake decreased for those with a cognitive impairment. Cognitive impairment significantly lowered odds of sight checks and dentist visits. Inequalities in sight and dental checks remain after factoring in accessibility. Routine health checks remain important even if facing other health challenges.